Odpowiedzi

2009-11-24T15:47:48+01:00
X⁹⁹ + x⁹⁸ + ... + x² + x --> to mozna policzyc jako sume ciągu arytmet. , czyli x+x⁹⁹/2 *99
/-kreska ułamkowa
(x-1) (x+x⁹⁹/2 *99+1)


2009-11-24T18:06:28+01:00
(x - 1)(x⁹⁹ + x⁹⁸ + ... + x² + x + 1)

Zauważ, że będzie:
x¹⁰⁰- x⁹⁹ + x⁹⁹ - x⁹⁸ + ... + x³ - x² + x² - x + x - 1
Wszystko się nam ładnie skróci, zostanie:
x¹⁰⁰ - 1
2009-11-24T21:27:43+01:00
Gdy mamy
x³-1=(x-1)(x²+x+1)
analogicznie bedzie

(x - 1)(x⁹⁹ + x⁹⁸ + ... + x² + x + 1)=
=x¹⁰⁰- x⁹⁹ + x⁹⁹ - x⁹⁸ + ... + x³ - x² + x² - x + x - 1=

=x¹⁰⁰ - 1